Rationale for Utilization of Hydrogel Rectal Spacers in Dose Escalated SBRT for the Treatment of Unfavorable Risk Prostate Cancer - Repka, Michael C.; Creswell, Michael; Lischalk, Jonathan W.; Carrasquilla, Michael; Forsthoefel, Matthew; Lee, Jacqueline; Lei, Siyuan; Aghdam, Nima; Kataria, Shaan; Obayomi-Davies, Olusola; Collins, Brian T.; Suy, Simeng; et al. (Frontiers in Oncology, 2022)
In this review we outline the current evidence for the use of hydrogel rectal spacers in the treatment paradigm for prostate cancer with external beam radiation therapy. We review their development, summarize clinical evidence, risk of adverse events, best practices for placement, treatment planning considerations and finally we outline a framework and rationale for the utilization of rectal spacers when treating unfavorable risk prostate cancer with dose escalated Stereotactic Body Radiation Therapy (SBRT).